Pulse detection sensor with green light transceiver integrated optoelectronic chip - Chenchen ZHANG; Xumin GAO; Ziqi YE; Mingming BO; Zefeng HU; Yongjin WANG (物联网学报)
Photo plethysmo graphy (PPG) is widely used to detect heart rate and pulse activity due to its simple design, low cost, and signal cycle that can effectively reflect the heart rhythm.Owing to the partial overlap between the emission and the detection spectra of GaN multiple quantum well (MQW) diode, the MQW receiver can respond to the light emitted from the transmitter sharing identical MQW structures.Thus, the fabricate and characterize monolithic integration of GaN transmitter and receiver was proposed as a single unit onto a conventional GaN-on-sapphire platform.This not only can effectively reduce the size and cost of the device, but also fully improves the sensitivity of the system.The experimental results show that the gallium nitride integrated optoelectronic chip can effectively receive the reflected light modulated by the heart pulse.Combined with circuit processing, the tester’s heart rate and pulse beat frequency can be calculated according to the restored PPG signal, so as to play the role of detection and warning.